Система транспортного обслуживания логистической системы - Ольхова, Марія Володимирівна; Горяинов, А. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
Going is presented near the system of a transport service. Predlo-wives a variant of the system of a transport service is «producer-users». Going is formed near the choice of priorities of maintenance of the logistic systems.